Stakeholder Mapping Analysis on the Scaling-Up Nutrition Movement during the 1000 Days of Life between the Urban and Rural Government Areas - Sriatmi, Ayun; Jati, Sutopo Patria; Suryoputro, Antono; Fatmasari, Eka Yunila (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
The Scaling-Up Nutrition (SUN) Movement was an intervention to overcome chronic malnutrition through integrated stakeholder collaboration. Furthermore, the roles of stakeholders' in the SUN-Movement were not optimal and their characteristics were not yet known based on the groups and government areas (cities and regency). This study aims to map the SUN-Movement stakeholders' roles in different groups and government areas based on their attitudes, powers, and interests. This is an observational descriptive research with a qualitative approach. Totally of 30 institutions as stakeholders were involved in this study and divided into 3 different groups, namely Decision Maker (DM), Provider (P), and Clients & Representatives (CR). The DM group have the power to influence programs. Also, the P group was better at handling technical issues, however, it cannot build collaboration with other stakeholders. The CR tend to build this collaboration passively, nevertheless, it does not consider the SUN-Movement to be important. Consequently, each stakeholder views their roles differently. Different perceptions about stakeholders' roles in various indicators and government areas reveals an implementation gap in the SUN-Movement. Therefore, in conclusion, strengthening advocacy, coordination, routine socialization, and communication between stakeholders could bridge the needs, constraints and challenges that cause malnutrition and stunting.